Seroepidemiological Study of Toxoplasmosis in Women Referred to Arak Marriage Consulting Center during 2012-2013 - Alireza Mohammadi; Saeedeh Shojaee; Mahboobeh Salimi; Mehdi Zareei; Mehdi Mohebali; Hossein Keshavarz (Tehran University of Medical Sciences, 2015)
Background: Toxoplasmosis is a zoonotic and usually asymptomatic infection. This study was carried out to investigate the seroepidemiology of Toxoplasma infection in women referred to Arak Marriage Consulting Center during 2012-2013. Methods: In this cross-sectional study, serum samples were collected from 400 women referred to Marriage Consulting Center in Arak City, Markazi Province, central Iran during 2012-2013. Anti-Toxoplasma IgG and IgM antibodies were measured by ELISA using homemade antigen. Results were analyzed by SPSS 18 and the correlation between toxoplasmosis and some affecting factors were estimated. Results: Overall, 97 cases (24.3%) had IgG antibodies against T. gondii and 19 cases (4.8%) were positive for IgM antibodies. A significant correlation was seen between T. gondii infection with clinical symptoms, keeping cat as pet animal, education and handling or eating raw or undercooked meat (P < 0.05). Conclusion: The prevalence of (24.3%) for Toxoplasma infection was seen in Arak City. It seems that keeping cat as pet and consumption of undercooked liver and uncooked hamburger are the most important transmission routes for the infection in this city. Since the majority of women are Toxoplasma sero-negative (75.7%) in Arak City, using serological tests and health education prior to marriage or during pregnancy is recommended.